2019
DOI: 10.1055/s-0039-1697069
|View full text |Cite
|
Sign up to set email alerts
|

Medial Wedge Opening High Tibial Osteotomy with an Extra Screw Fixation

Abstract: Medial wedge opening high tibial osteotomy (MWOHTO) is effective for managing a variety of knee conditions, varus malalignment of the knee, either secondary to osteoarthritis or residual adolescent tibia vara, are among the indications, fixation may be done using different methods (Stables, T-plate, Budu plate, and TomoFix). We are describing our technique of performing (MWOHTO) fixed with titanium T plate supplemented with an extra screw from the lateral side which we call “extra-focal” screw to obtain bipla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…5 All authors performing metaphyseal osteotomy for Blount`s correction concluded that the metaphyseal osteotomy used to correct a physeal deformity results in the need for lateral translation at the osteotomy site, thus particularly in larger deformities it will be difficult to hold the correction with a plate. [13][14][15] Asymmetrical physeal distraction with a monolateral fixator is also used for treatment of adolescent tibia vara. In all cases, the distraction had resulted in proximal tibial growth plate closure and carried risk of septic knee.…”
Section: Discussionmentioning
confidence: 99%
“…5 All authors performing metaphyseal osteotomy for Blount`s correction concluded that the metaphyseal osteotomy used to correct a physeal deformity results in the need for lateral translation at the osteotomy site, thus particularly in larger deformities it will be difficult to hold the correction with a plate. [13][14][15] Asymmetrical physeal distraction with a monolateral fixator is also used for treatment of adolescent tibia vara. In all cases, the distraction had resulted in proximal tibial growth plate closure and carried risk of septic knee.…”
Section: Discussionmentioning
confidence: 99%